Inflammation, Immune Senescence, and Dysregulated Immune Regulation in the Elderly - Shive, Carey; Pandiyan, Pushpa (Frontiers in Aging, 2022)
An optimal immune response requires the appropriate interaction between the innate and the adaptive arms of the immune system as well as a proper balance of activation and regulation. After decades of life, the aging immune system is continuously exposed to immune stressors and inflammatory assaults that lead to immune senescence. In this review, we will discuss inflammaging in the elderly, specifically concentrating on IL-6 and IL-1b in the context of T lymphocytes, and how inflammation is related to mortality and morbidities, specifically cardiovascular disease and cancer. Although a number of studies suggests that the anti-inflammatory cytokine TGF-b is elevated in the elderly, heightened inflammation persists. Thus, the regulation of the immune response and the ability to return the immune system to homeostasis is also important. Therefore, we will discuss cellular alterations in aging, concentrating on senescent T cells and CD4+ CD25+ FOXP3+ regulatory T cells (Tregs) in aging.